Individual differences in echocardiography: Visual object recognition ability predicts cue utilization. Issue 6 (31st July 2020) - Carrigan, Ann J.; Stoodley, Paul; Fernandez, Fernando; Sunday, Mackenzie A.; Wiggins, Mark W.
Summary: Echocardiographers are highly specialised, skilled practitioners who play a critical role in medical imaging diagnostics. Yet, little is known about the cognitive and perceptual attributes of experts within this domain. This study was designed to examine the role of individual differences in expertise. Specifically, the contribution of a domain general visual expertise and pattern recognition, or cue utilization. Data were collected from 42 echocardiographers and 43 naïve participants. All of the participants competed the Novel Object Memory Test (NOMT). When compared, the echocardiographers were more accurate than the naïve participants. The echocardiographers also completed an echocardiography edition of the Expert Intensive Skills Evaluation 2.0, to establish behavioral indicators of context‐related cue utilization. Those with relatively higher cue utilization performed more accurately on the NOMT, controlling for exposure. These results suggest that a general perceptual ability contributes to echocardiography potential and a sensitivity to cue‐based learning may contribute to expertise.